Jejak Praktik Berekonomi Islam Dalam Masyarakat Muslim Indonesia dan Masa Depannya - Nur Kholis (Unisia, 2011)
This article proposes to elaborate and describe the clue of Islamic economic practice In Indonesian moslem society and analyze its future. Some economic activities practiced by Indonesian moslem, after Islam spreadied in Indonesia, identified based on fiqh muamalah rules that nature rules of Islamic economics. Some of their economics activities done by practicing profit sharing mechanism, avoiding riba/interest, down payment basedon bay'al-urbun, bay'al-istisna'etc. Although there are some fact that Islamic economic norms practiced by Indonesian moslem, the government of Indonesia in the era of New Orderand the beginning of reformation era did not support the development of Islamic economic. It effected the practice of Islamic economics in Indonesia was amending slowly. Last ten years, support of Indonesian government to develop Islamic economic practice was significance. It effected the development of Islamic economic practice in many sectors offinance and business is very impressed. It means that the influence of the islamic political economy of Indonesian government to the development of Islamic economic practice in the Indonesian society is very signifinace.